On the Issue of Components of Personal Maturity - Alla А. Gudzovskaya; Viktoriya V. Shpuntova (Rossijskij psihologičeskij žurnal., 2016)
The authors analyzed the problems of the formation of personal maturity and made an assumption that the components of personal maturity (ego-identity, active possession of the environment, and self-actualization) would be formed atthe age of seven or eight. The paper presents the results of a longitudinal study of the components ofpersonal maturity. The longitudinal group included 232 pupils of the rst form of comprehensive schools of Samara and Tolyatti; 96 persons of them took part in all the longitudinal sections of the study. The authors carried out the rst study in 1997–1998, when the respondents were pupils of the rst form. In the nal study (2014–2015) all the subjects graduated from high schools, as well as higher/ secondary educational institutions (at the age from 24 to 25). To study the components of personal maturity the authors asked respondents to write a composition with the following title: “I Am a Human Being”, and also used the method of ultimate senses by D. A. Leont’ev, content analysis, and method of expert evaluations. The study showed that the formation of personal maturity takes place when dealing with life’s challenges and building relationships with the world (society). Theperson realizes himself/herself, generates an image of a human being as abearer of social roles, recognizes his/her own involvement in culture and inuences himself/herself and others through various forms of internal and external activity; he/she is the author of the inner world. The results of the empirical study showed that the developed ego-identity, active possession of the environment (the ability to behave regardless the inuencing circumstances and pursue his/her own aims), and selfactualization were the components of personal maturity. These components are basically formed at the age of seven or eight. The ndings of the study could be useful for psychologists, pedagogues, and social workers. The basic propositions of this paper have great potential for correctional and developing work of a school psychologist for optimizing the educational process.